Following the Students' Lead: Exploring the Value of Incentives - Greta Davis (Networks: An Online Journal for Teacher Research, 2003)
Recently, I decided to focus on how children perceive the learning activities I give them. I believed this would not only help improve my students' metacognitive skills by encouraging them to identify what strategies best helped them to learn but it would also help my practice by understanding how my goals for activities might differ from their goals. I shared this interest with the students at the beginning of the year and asked for their assistance in exploring these issues. I planned to use a means of data collection that my DICEP colleagues had proposed. It involved pausing or "freezing" a learning session so that open dialogue could occur and the class's thoughts regarding an activity could be recorded. I felt it would be important to discover what the students felt was the purpose of the activity and what they thought they were learning while in the middle of the activity. I hoped the data would allow me to begin to explore if our perceived purpose of the activity was similar of different. I also wanted to know if the students felt the activity was meeting their learning needs. I wondered what types of learners were in my classroom and if they knew what types of learners they were.